Plagiarism in EFL Academic Writing: Students' self-reported reasons for internet plagiarism - Malikhatul Lailiyah; Prilla Lukis Wediyantoro (Universitas Merdeka Malang, 2022)
Studies show that students who cheat at certain levels of education are more likely to do so at work or at later levels of education. One form of academic fraud is plagiarism. Some researchers claim that students deliberately plagiarize, while others plagiarize because they do not understand how to properly cite, paraphrase, or refer to sources. Therefore, this study aims to understand English as a Foreign Language (EFL) students' self-reported reason for internet plagiarism in Academic Writing class, as understanding the causes of student plagiarism is essential to properly addressing the problem. To obtain the data, a survey of respondents' reason for plagiarize was distributed to second, fourth and sixth trimester students of the Department of English in a private university. A total of 85 students participated in the survey. As a result, we found that some people, despite having a high level of understanding of plagiarism, admitted to intentionally plagiarizing for various reasons. Additionally, research shows that people do not understand that claiming work from a source as their own without acknowledging the source is part of plagiarism.DOI: 10.26905/enjourme.v7i2.8640